Al-Mar’ah fi al-Qur’ân ‘Inda Ibn ‘Asyûr fi Tafsîrih (Dirâsah ad-Dilâlah al-Qur’âniyyah) - Ali Mahfuz Munawar; Dyah Nurul Azizah (Universitas Darussalam Gontor, 2017)
There are various studies about al-Mar’ah in the Qur’an, also the term that is used for the context of mar’ah, including imra’ah and nisâ’. With the semantic approach, Ibnu Asyur tries to study this theme is according to imra’ah and an-nisâ’. This paper found that term imra’ah has a more specific meaning than